Comparison Analysis on the Success Rate of NPF and NPL in Microfinancing: Study Case of Bank Rakyat Indonesia (BRI) and BRI syariah - Atiqi Chollisni Nasution; Dwi Kartika (ISLAMINOMICS: JOURNAL OF ISLAMIC ECONOMICS, BUSINESS AND FINANCE, 2013)
This study aims to investigate and demonstrate empirically on thesuccess rate ratio of non-performing loan (NPL) or non-performingfinancing (NPF) micro financing between PT. BRISyariah Bankand PT. Bank Rakyat Indonesia (Persero) Tbk., During the periodDecember 2009 to 2012. This study is a comparative descriptivestudy. The data are secondary data in the form of financialstatements of earning assets by Bank Indonesia. Data analysis wasperformed using analysis of the ratio of Non Performing Financing(NPF) and NPL. Techniques analysis which used to compare thelevel of success NPF of microfinance BRI Shariah and BRI isMann-Whitney Test Method. The result shows that there aresignificant differences in the success rates of NPF micro financingbetween BRI Shariah and BRI. The study also concludes that thelevel of NPF/NPL of BRI Shariah is more eminent compare to BRI.However, refers to the provisions of Bank Indonesia that healthyor good NPF/NPL is ≤ 5%, BRI is still in ideal condition.